Bioindicadores ambientales de la incidencia del cambio climático y saberes ancestrales en el cantón Pujilí - Chicaiza Rengifo, Tatiana Geovanna (2016)
The purpose of the investigation was to know the local environmental bio indicators that exist in the surrounding areas to Pujilí canton, their conservation and incidence of the climate changes. The investigation was realized in three communities of the Pujilí canton: La Merced, Alpamalag and La Victoria, in the academic period April-August 2016 with the objective of documenting the ancestral knowledge of the signals or bio indicators environmental that they used to interpret and predict climate change, already that in the current situation these knowledge to be forget by the new farmer generation.